1988
DOI: 10.1128/mcb.8.1.347
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mutation in mouse FM3A cells by N4-aminocytidine-mediated replicational errors.

Abstract: To explore the potential use of a nucleoside analog, N4-aminocytidine, in studies of cellular biology, the mechanism of mutation induced by this compound in mouse FM3A cells in culture was studied. On treatment of cells in suspension with N4-aminocytidine, the mutation to ouabain resistance was induced. The major DNA-replicating enzyme in mammalian cells, DNA polymerase a, was used to investigate whether the possible cellular metabolite of N4-aminocytidine, N4-aminodeoxycytidine 5'-triphosphate (dCa`TP), can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…It was reported that the triphosphates of N 4 -hydroxycytidine (ho 4 C), N 4 -methoxycytidine (mo 4 C) and N 4 -methylcytidine (m 4 C) exhibited ambiguous properties in polymerization (2224), and N 4 -aminodeoxycytidine triphosphate can be incorporated in place of both dCTP and dTTP (25,26). We have found that 4-semicarbazidocytidine triphosphate, a N 4 -aminocytidine derivative, can be incorporated as UTP by phage RNA polymerase (27) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the triphosphates of N 4 -hydroxycytidine (ho 4 C), N 4 -methoxycytidine (mo 4 C) and N 4 -methylcytidine (m 4 C) exhibited ambiguous properties in polymerization (2224), and N 4 -aminodeoxycytidine triphosphate can be incorporated in place of both dCTP and dTTP (25,26). We have found that 4-semicarbazidocytidine triphosphate, a N 4 -aminocytidine derivative, can be incorporated as UTP by phage RNA polymerase (27) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…DCyt і 4 meCyt, фе но ме но логічні ефек ти му та ген ної дії яких на й кра ще з-поміж спо лук ана логічної будо ви пред став ле но в літе ра турі [6][7][8][9][10][11][12]. Пред мет вив чен ня -фізи ко-хімічна при ро да про цесів внутрішньо мо ле ку ляр ної та у то ме ри зації зазначених му та генів та їхні кон фор маційні влас ти вості, включа ю чи струк тур ну не жорсткість.…”
unclassified
“…The cis relationship between the N 4 substituent and N 3 appears to be a common feature among N4-substituted 2'-deoxycytidine analogues (Takahashi et al, 1988;Jia et al, 1990b;Audette et al, 1997;Audette et al, 1998).…”
mentioning
confidence: 99%